Communication and quality service delivery in Uganda's local government - Balunywa, Waswa (Routledge, 2014)
The study aimed at understanding the role of total quality management (TQM) as a mediator between communication and quality service delivery (QSD) in Uganda’s local government (LGs). Data were collected using a cross-sectional research design from 212 LGs whose heads of department and section heads formed the unit of inquiry. The paper utilises the Med Graph program, Sobel’s z-test and the Kenny and Baron procedure to test the role of TQM as a mediator between communication and QSD. The findings revealed that TQM is a significant mediator between communication and QSD, and enhances the relationship by 24.3%. In addition, a partial type of mediation was established. Overall, the results show that communication predicts QSD directly and also indirectly via TQM. The study was cross-sectional with its inherent flaws. Future studies should consider mediation studies from a longitudinal perspective. In addition, the data were collected only from Uganda’s LGs. Therefore, the findings may be limited to the sample studied and negate the possibility of generalisation. In terms of practical implications, LG managers should consider TQM as stimuli for communication to ensure QSD. The paper contributes to the service literature by extending the role of communication for QSD within the context of LGs whose empirical stance is still scanty. In addition, it contributes to literature on TQM by highlighting its mediatory role for QSD in LGs.
: the mediating influence of total quality management
Keywords: Communication; Local government; Quality service delivery; Total quality management